ANALISIS PENANGANAN TINDAK PIDANA PENYELUNDUPAN BABY LOBSTER DI KPPBC TMP JUANDA (STUDI KASUS PUTUSAN NOMOR 760/PID.B/2023/PN SDA) - Suantono; M. Syahrul Borman; Dudik Djaja Sidharta; Irawan Soerodjo (Fakultas Hukum, Universitas Semarang, 2025)
This research aims to analyze the handling of baby lobster smuggling crimes that occur in the KPPBC TMP Juanda working area, with a focus on the case study of Decision Number 760/Pid.B/2023/PN Sda. Misuse of fisheries resources, such as baby lobster smuggling, has significantly impacted the marine ecosystem and the national economy, especially for fishermen. This study evaluates the implementation of the law applied, the obstacles faced by law enforcement officers, as well as the effectiveness of law enforcement in this case. The results showed that the defendant, Andy Dewi Hardianto, was proven to have violated Article 102A letter a of the Customs Law and Article 55 paragraph (1) to 1 of the Criminal Code for smuggling more than 50,000 lobster seeds without valid customs documents. The Panel of Judges imposed a sentence of two years imprisonment and a fine of Rp500,000,000, with a provision for two months' imprisonment. The main obstacles in handling this case include weak supervision, limited apparatus resources, and the complexity of the international smuggling network. Abstrak Penelitian ini bertujuan untuk menganalisis penanganan tindak pidana penyelundupan baby lobster yang terjadi di wilayah kerja KPPBC TMP Juanda, dengan fokus pada studi kasus Putusan Nomor 760/Pid.B/2023/PN Sda. Penyalahgunaan sumber daya perikanan, seperti penyelundupan baby lobster, telah memberikan dampak negatif signifikan terhadap ekosistem laut dan perekonomian nasional, khususnya bagi para nelayan. Studi ini mengevaluasi implementasi hukum yang diterapkan, hambatan yang dihadapi aparat penegak hukum, serta efektivitas penegakan hukum dalam kasus ini. Hasil penelitian menunjukkan bahwa terdakwa, Andy Dwi Hardianto, terbukti melanggar Pasal 102A huruf a Undang-Undang Kepabeanan dan Pasal 55 ayat (1) ke-1 KUHP atas penyelundupan lebih dari 50.000 benih lobster tanpa dokumen pabean yang sah. Majelis Hakim menjatuhkan pidana dua tahun penjara dan denda Rp500.000.000, dengan ketentuan pengganti kurungan dua bulan. Kendala utama dalam penanganan kasus ini meliputi lemahnya pengawasan, keterbatasan sumber daya aparat, dan kompleksitas jaringan penyelundupan yang bersifat internasional.